Axial compressive behavior of seawater sea-sand recycled aggregate concrete-filled double-skin non-corrosive tubular columns with square cross-section. (October 2021) - Li, Pengda; Zhou, Yingwu; Yang, Tianqi; Yang, Qiaofei; Xing, Feng
Abstract: This paper presents the results of an experimental investigation on mechanical properties of seawater sea-sand recycled aggregate concrete (SSRAC) filled double-skin tubular square columns (DSTCs). A total of 45 square DSTCs, included 12 fully-filled FRP confined SSRAC (fiber-reinforced polymer) columns, 21 FRP-SSRAC-aluminum tube columns, and 12 FRP-SSRAC-stainless steel tube columns, were tested under axial compression. The effects of the key parameters, including void ratio, recycled aggregate (RA) replacement ratio, and tube materials' properties, on the structural behavior of SSRAC-filled square DSTCs are discussed. The test results indicate that mixing seawater and sea-sand with RAs could make up the early strength reduction caused by RA replacement. The void ratio significantly influences the stress–strain relationship of SSRAC filled in DSTCs due to the nonuniform hoop confinement pressure caused by the square cross-section. This nonuniform hoop confinement is also highly related to the inner tubes' material properties due to their different local buckling behaviors. The test results are also used to assess the suitability of existing models proposed for different kinds of DSTCs. The evaluation results suggest that the models could provide satisfying predictions as long as the corner radius and void ratio's coupling effects are reasonably considered. Highlights: Inner tube material affects the mechanical properties of the confined SSRAC. The inner void ratio influences the stress-strain behavior of square SSRAC. The effects of RAs replacement ratio alter with inner tube materials' properties. The FRP rupture strain is dependent on the void ratio and RAs replacement ratio.